Pengaruh pelatihan tenaga gizi puskesmas terhadap program keluarga sadar gizi di Kota Samarinda Provinsi Kalimantan Timur - Sri Sedono Iswandi; Endy Paryanto Prawirohartono; Abidillah Mursyid (Jurnal Gizi Klinik Indonesia, 2007)
Background: Under nutrition remains a major malnutrition problem in Indonesia. In dealing with the problem, the Indonesian government has already implemented strategies including empowering health workers and families. It is very likely that the nutrition problem and the family awareness on nutrition are closely related. Families that practice balanced nutrition are able to recognize and cope with their nutrition problems are defined as nutritionally aware or better known as Kadarzi.